Prevalensi Hipertensi Pada Lansia di Desa Prambatan dan Upaya Intervensi Melalui Edukasi dan Layanan Kesehatan Oleh Mahasiswa KKN - Eko Jaswanto; Rara Verna A; Tutut Riyani; Renti Puspitasari; Rika Dahlia; Daffa Dewangga A; Putri Aprillia U; Aprilia Azzahra; Yiving Ircha; Aliya Agustina; Zera Mutiara; Laeli Marifah; Afriani Setya N; Rio Candra P; Irma Suryani; Winda Nursanti (JURNAL PENGABDIAN KADER BANGSA, 2026)
Hypertension is one of the main health problems often experienced by the elderly and can increase the risk of serious complications such as heart disease and stroke. This study aims to analyze the level of risk of hypertension in the elderly in Prambatan Village, Abab District, Panukal Abab Lematang Ilir Regency (PALI), South Sumatra. The method used was a quantitative approach with survey techniques and interviews with elderly people who met the inclusion criteria. Data were collected through blood pressure checks, medical history, and lifestyle factors such as diet and physical activity.The results showed that most of the elderly in this village have a high risk of hypertension, which is influenced by a high-salt diet, lack of physical activity, and a family history of hypertension. In addition, low awareness about hypertension prevention is one of the factors that worsen this condition. Therefore, health education on healthy lifestyle and regular blood pressure monitoring are needed to reduce the risk of hypertension in the elderly in this area.